Sulfur-resistant corrosion-resistant low-carbon alloy coiled tubing and preparation method thereof

Through plasma welding and heat treatment processes, the tensile strength and corrosion resistance of CT80 continuous oil pipes are improved, and the problem of insufficient strength and corrosion resistance of existing oil pipes in hydrogen sulfide well fields is solved, thus achieving higher oil and gas resource mining efficiency.

CN119407313APending Publication Date: 2025-02-11XINDA KECHUANG TANGSHAN PETROLEUM EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703563.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing CT80 continuous oil pipes have problems such as low strength, short life, and insufficient sulfur corrosion resistance in hydrogen sulfide well fields, which are difficult to meet the demand for oil and gas resource mining in complex wells.

Method used

Through plasma welding and optimized heat treatment process, the grain refinement and tissue uniformity of steel strip welds are improved, and sulfur-resistant, corrosion-resistant low-carbon alloy continuous oil pipes are prepared, with the comprehensive performance reaching 90 steel grades.

Benefits of technology

It significantly improves the tensile strength, yield strength and corrosion resistance of the continuous oil pipe, which is better than the traditional CT90 continuous oil pipe, and can maintain good corrosion resistance in 95%N2+5%O2 environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407313A_ABST
    Figure CN119407313A_ABST
Patent Text Reader

Abstract

The invention provides a sulfur-resistant corrosion-resistant low-carbon alloy coiled tubing and a preparation method thereof, and relates to the technical field of coiled tubing. By means of the plasma welding mode, steel strip weld joint grains are refined, the structure is uniform, the strength is stable, and the strength and corrosion resistance of a plate connector are prevented from being reduced. According to the heat treatment process, weld grains are refined, the structure is more uniform, stress is removed, the strength of the whole pipe is stable, the structure is uniform, and the final purposes of high strength and high corrosion resistance are achieved. The metallographic structure of the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing is ferrite and pearlite, the average grain size of metal in a weld joint, a heat affected zone and a base material reaches 10.0 grade or above, and the comprehensive performance can reach 90 steel grade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coiled tubing, and in particular to a sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing and a preparation method thereof. Background Art

[0002] At present, oil and gas drilling and production generally use CT80 continuous tubing. CT80 continuous tubing is generally made of low-carbon and low-manganese steel strips, and is made by high-frequency welding or laser welding. The steel grade strength only reaches 80 steel grade. Therefore, although CT80 continuous tubing can meet the use environment of hydrogen sulfide well field operations, it has low strength, short life, insufficient pressure and load bearing capacity, and insufficient sulfur resistance and corrosion resistance, which affects the resource extraction rate in the oil and gas field. As the well conditions of oil and gas resource extraction become more and more complex, CT80 continuous tubing is not enough to meet the needs of resource extraction. Summary of the invention

[0003] In view of this, the present invention provides a sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing and a preparation method thereof. The present invention improves the grain refinement and structural uniformity of the steel strip weld through plasma welding and optimized heat treatment process, so that the tensile strength, yield strength and corrosion resistance of the coiled tubing are significantly improved, which is better than the traditional CT90 coiled tubing, and the comprehensive performance can reach 90 steel grade.

[0004] The sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing provided by the present invention is manufactured by butting steel strips, curling, tube blank welding, extrusion, weld seam heat treatment, and cooling. The sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing includes, by mass percentage:

[0005] C 0.04%~0.08%, Mn 1.5%~2.0%, Si 0.1%~0.3%, Cr 0.1%~0.3%, Mo0.05%~0.3%, Nb 0.04%~0.07%, Ti 0.005%~0.025%, Al 0.01%~0.05%, Ni≤0.3%, Cu≤0.3%, P≤0.02%, S≤0.02%, the balance is Fe and unavoidable impurities.

[0006] The present application also provides a method for preparing the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing, comprising the following steps:

[0007] S1. The steel strip is extended by butt welding, and the weld area is subjected to rolling deformation heat treatment;

[0008] S2, curling the steel strip obtained in S1 to form a round tube blank with a weld;

[0009] S3, welding the round tube obtained in S2, adding an extrusion roller to the unsolidified rear of the molten pool to extrude the weld into shape;

[0010] S4. The weld formed by the extrusion in S3 is heat treated, and after air cooling to room temperature, a sulfur-resistant and corrosion-resistant low-carbon alloy continuous oil pipe is obtained.

[0011] Preferably, the butt welding in S1 is performed by plasma welding, and the welding wire used is a manganese-molybdenum steel high-strength copper-plated welding wire.

[0012] Preferably, the rolling deformation heat treatment in S1 refers to rolling the weld area while performing heat treatment, the rolling pressure is 4 to 8T, the rolling deformation heat treatment is repeated once, the rolling deformation heat treatment temperature is 600°C to 750°C, and the insulation time for a single rolling heat treatment is 10 seconds.

[0013] Preferably, the welding in S3 is laser welding or high frequency welding.

[0014] Preferably, the heat treatment in S4 is simulated normalizing and tempering treatment, wherein the treatment temperature of the simulated normalizing is 900°C to 940°C, the furnace is heated by induction heating, the heating coil length is 1.5m, the running speed is 2.8m / min, and air cooling is performed after heating. The air cooling section is 50m long and then enters the water cooling zone to cool to room temperature. The tempering treatment temperature is 500°C to 600°C, the insulation section length of the tempering furnace is 4m, and the insulation time is 79.8s.

[0015] Compared with the prior art, the present invention refines the grains of the steel strip weld, makes the structure uniform, and stabilizes the strength through plasma welding, thus avoiding the reduction of the plate interface strength and corrosion resistance. At the same time, the heat treatment process of the present invention refines the weld grains, makes the structure more uniform, removes stress, stabilizes the strength of the whole pipe, and makes the structure uniform, thus achieving the ultimate goal of high strength and strong corrosion resistance.

[0016] The pipe body of the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing of the present invention is equivalent to the pipe body of the CT90 coiled tubing in terms of HIC cracking resistance, SSC cracking resistance and corrosion resistance in a 95% N2+5% O2 environment. The pipe body of the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing of the present invention has a tensile strength greater than 669MPa, a yield strength greater than 620MPa, an average hardness of 95HRB, a metallographic structure of ferrite+pearlite, and an average metal grain size of 10.0 or above in the weld, heat-affected zone and parent material, which can reach 90 steel grade. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention will be further described below in conjunction with the accompanying drawings.

[0018] Figure 1 The weld of Example 1 of the present invention is divided into equal sections;

[0019] Figure 2 The weld of comparative example 1 of the present invention is divided into equal sections;

[0020] Figure 3 This is the sample of Example 1 in Test Example 2 before cleaning the corrosion products;

[0021] Figure 4 The sample of Example 1 in Test Example 2 after cleaning the corrosion products;

[0022] Figure 5 This is the CT90 sample in Test Example 2 before cleaning the corrosion products;

[0023] Figure 6 This is the CT90 sample in Test Example 2 after the corrosion products are cleaned;

[0024] Figure 7 It is the sample surface at the weld in Test Example 3;

[0025] Figure 8 This is the metallographic image of the equally divided section at the weld in Test Example 3;

[0026] Fig. 9 The surface of the specimen at 90° from the weld in Test Example 3;

[0027] Fig.10 This is the metallographic image of the equally divided section at 90° from the weld in Test Example 3;

[0028] Fig.11 The surface of the specimen at 180° from the weld in Test Example 3;

[0029] Fig.12 This is the metallographic image of the equally divided section at 180° from the weld in Test Example 3;

[0030] Fig.13 This is the surface (front) of the CT80-2 sample after 96h corrosion test;

[0031] Fig.14 This is the surface (back side) of the CT80-2 sample after 96h corrosion test;

[0032] Fig.15 This is the surface (front side) of the sample in Example 1 after 96h corrosion test;

[0033] Fig.16 This is the surface (back side) of the sample in Example 1 after the 96h corrosion test;

[0034] Fig.17 This is the surface (front side) of the CT80-1 sample after 96h corrosion test;

[0035] Fig.18 This is the surface (back side) of the CT80-1 sample after 96h corrosion test;

[0036] Fig.19 This is the surface (front side) of the CT90 sample after 96h corrosion test;

[0037] Fig. 20 This is the surface (back side) of the CT90 specimen after 96h corrosion test;

[0038] Fig.21 This is a typical metallographic crack on the cross section of the CT80-1 specimen;

[0039] Fig. 22 This is a typical metallographic crack on the cross section of the CT90 specimen;

[0040] Fig.23 This is the surface of CT80-2 sample after 720h corrosion test;

[0041] Fig.24 This is the surface of the sample in Example 1 after 720h corrosion test;

[0042] Fig.25 This is the surface of CT80-1 sample after 720h corrosion test;

[0043] Fig.26 This is the surface of the CT90 sample after 720h corrosion test. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention provides a sulfur-resistant and corrosion-resistant low-carbon alloy coiled oil pipe, which is manufactured by butting steel strips, curling, tube blank welding, extrusion, weld heat treatment, and cooling. The sulfur-resistant and corrosion-resistant low-carbon alloy coiled oil pipe of the present invention comprises, by mass percentage:

[0046] C 0.04%~0.08%, Mn 1.5%~2.0%, Si 0.1%~0.3%, Cr 0.1%~0.3%, Mo0.05%~0.3%, Nb 0.04%~0.07%, Ti 0.005%~0.025%, Al 0.01%~0.05%, Ni≤0.3%, Cu≤0.3%, P≤0.02%, S≤0.02%, the balance is Fe and unavoidable impurities.

[0047] In the coiled tubing of the present invention, the C content affects the corrosion rate and hardness of the coiled tubing. The higher the carbon content, the more micro-electrochemical cells are formed. The faster the corrosion rate of carbon steel is, the lower the carbon content is, and the basic strength (hardness) of carbon steel is low. Therefore, the present invention controls the carbon content to 0.04% to 0.08% to seek a balance between the corrosion resistance and strength of the coiled tubing; the role of Mn is to increase the strength of carbon steel; the role of Si is to avoid the reduction of toughness; the role of Ti and Al is to refine the grains. Compared with conventional CT90 raw materials, the present invention makes the coiled tubing have stronger corrosion resistance by adjusting the elements.

[0048] The present application also provides a method for preparing the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing, comprising the following steps:

[0049] S1. The steel strip is extended by butt welding, and the weld area is subjected to rolling deformation heat treatment;

[0050] S2, curling the steel strip obtained in S1 to form a round tube blank with a weld;

[0051] S3, welding the round tube obtained in S2, adding an extrusion roller to the unsolidified rear of the molten pool to extrude the weld into shape;

[0052] S4. The weld formed by the extrusion in S3 is heat treated, and after air cooling to room temperature, a sulfur-resistant and corrosion-resistant low-carbon alloy continuous oil pipe is obtained.

[0053] The butt welding method in S1 of the present invention is preferably plasma welding, and the welding wire used is preferably manganese-molybdenum steel high-strength copper-plated welding wire. The present invention uses plasma welding to achieve the purpose of single-sided welding and double-sided forming, avoids oxidation of alloy steel, and has high penetration depth and can weld various wall thickness plates.

[0054] The rolling deformation heat treatment described in S1 of the present invention refers to rolling the weld area while performing heat treatment, the rolling pressure is 4-8T, the rolling deformation heat treatment temperature is 600℃-750℃, and the single rolling heat treatment holding time is 10 seconds. The present invention adopts the rolling deformation heat treatment method to make the weld grains refined, the structure uniform, the strength stable, and avoid the reduction of the plate interface strength and corrosion resistance.

[0055] In some specific embodiments of the present invention, the weld gap of S2 is 1 to 2 mm.

[0056] The welding in S3 of the present invention is preferably laser welding or high frequency welding.

[0057] The heat treatment obtained in S4 of the present invention is simulated normalizing and tempering treatment, wherein the heat treatment in S4 is simulated normalizing and tempering treatment, wherein the treatment temperature of the simulated normalizing is 900°C to 940°C, the furnace is heated by induction heating, the length of the heating coil is 1.5m, the running speed is 2.8m / min, air cooling is performed after heating, the air cooling section is 50m long, and then enters the water cooling zone to cool to room temperature, the tempering treatment temperature is 500°C-600°C, the tempering furnace insulation section length is 4m, and the insulation time is 79.8s. In some specific embodiments of the present invention, the treatment temperature of the simulated normalizing is 910°C, and the tempering treatment temperature is 550°C. In other preferred embodiments of the present invention, the treatment temperature of the simulated normalizing is 940°C, and the tempering treatment temperature is 550°C.

[0058] The present invention adopts the method of extrusion + laser welding or high-frequency welding. During the coiling process, the steel strip is gradually rolled up by roller rolling to form a round tube blank with an open gap. The pressing amount of the extrusion roller is adjusted to control the weld gap to 1-2 mm, and welding is performed. After welding, an extrusion roller is added to the rear of the molten pool before it solidifies, and the rolling amount is increased until the gap at the edges of the two ends of the steel strip is 0. The welding is extruded and formed, and then the weld is heat treated to achieve the purpose of combining deformation strengthening and phase change strengthening, thereby greatly improving the weld strength.

[0059] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available.

[0060] The CT80-1 involved in the specific implementation of the present invention includes, by mass percentage:

[0061] C 0.046%, Si 0.162%, Mn 0.745%, P 0.011%, S 0.001%, Cr 0.558%, Ni 0.040%, Mo 0.184%, Cu 0.206%, W 0.004%, Ca 0.001%, V 0.006%, Ti 0.020%, Nb 0.017%, Al 0.041%, Zr 0.011%, Co 0.007%, B 0.00001%, As 0.008%, Pb 0.001%, Bi 0.023%, Sn 0.001%, Sb 0.074%, Bi 0.023%, and the balance is iron and inevitable impurities.

[0062] The CT80-2 involved in the specific implementation of the present invention includes, by mass percentage:

[0063] C 0.062%, Si 0.253%, Mn 0.763%, P 0.008%, S 0.001%, Cr 0.679%, Ni 0.144%, Mo 0.160%, Cu 0.262%, W 0.010%, Ca 0.001%, V 0.005%, Ti 0.017%, Nb 0.017%, Al 0.043%, Zr 0.008%, Co 0.009%, B 0.00001%, As 0.004%, Pb 0.001%, Bi 0.015%, Sn 0.001%, Sb 0.050%, Bi 0.015%, and the balance is iron and inevitable impurities.

[0064] The CT90 involved in the specific implementation of the present invention includes, by mass percentage:

[0065] C 0.123%, Si 0.405%, Mn 0.898%, P 0.006%, S 0.0001%, Cr 0.546%, Ni 0.056%, Mo 0.159%, Cu 0.243%, W 0.004%, Ca 0.001%, V 0.005%, Ti 0.035%, Nb 0.018%, Al 0.061%, Zr 0.011%, Co 0.006%, B 0.00001%, As 0.008%, Pb 0.002%, Bi 0.022%, Sn 0.002%, Sb 0.070%, Bi 0.022%, and the balance is iron and inevitable impurities.

[0066] Embodiment 1 A sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing comprises, by mass percentage:

[0067] C 0.0605%, Mn 1.7890%, Si 0.1675%, Cr 0.2080%, Mo 0.1375%, Nb 0.0620%, Ti 0.0100%, Al 0.0180%, Ni 0.0001%, Cu 0.0275%, P 0.0110%, S 0.0020%, and the balance is Fe and inevitable impurities.

[0068] The steps of the method for preparing the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing are as follows:

[0069] S1. The steel strip is connected by plasma welding. The welding wire is a manganese-molybdenum steel high-strength copper-plated welding wire. The weld area is subjected to rolling deformation heat treatment. The rolling pressure is 6T, and the rolling deformation heat treatment temperature is 735°C. The single rolling heat treatment holding time is 10 seconds. After the treatment is completed, it is air-cooled to room temperature.

[0070] S2, curling the steel strip obtained in S1 to form a round tube blank with a weld of (1.5±0.5) mm;

[0071] S3, laser welding the round tube obtained in S2, adding an extrusion roller to the unsolidified molten pool to extrude the weld into shape;

[0072] S4. The welds formed by extrusion in S3 were subjected to simulated normalizing heat treatment at 910°C and 940°C respectively. The simulated normalizing furnace was heated by induction heating. The heating coil length was 1.5m and the running speed was 2.8m / min. After heating, it was air-cooled. The air-cooling section was 50m long and then entered the water-cooling zone to cool to room temperature and then tempered at 550°C. The insulation section of the tempering furnace was 4m long and the insulation time was 79.8s. After air-cooling to room temperature, sulfur-resistant and corrosion-resistant low-carbon alloy continuous oil pipes were obtained.

[0073] Comparative Example 1

[0074] The same as Example 1, except that: the simulated normalizing temperature is 910° C., and in S3 only laser welding is performed without extrusion, specifically: laser welding is performed on the round tube blank obtained in S2.

[0075] Comparative Example 2

[0076] Same as Example 1, except that the simulated normalizing heat treatment temperature is 890°C.

[0077] Comparative Example 3

[0078] Same as Example 1, except that the simulated normalizing heat treatment temperature is 950°C.

[0079] Example 4

[0080] Same as Example 1, except that the simulated normalizing heat treatment temperature is 980°C.

[0081] Test Example 1

[0082] The coiled tubing and weld performances of 38.1 mm×3.7 mm obtained in Example 1 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.

[0083] Table 1 Test results of coiled tubing and weld performance

[0084]

[0085]

[0086] Test Example 2

[0087] The sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing raw material of Example 1 and the conventional CT90 steel plate were subjected to nitrogen and oxygen environment corrosion tests, and the test conditions were: N2 content 95%, O2 content 5%, total pressure 10MPa, temperature 150°C, solution 5% NaCl, and cycle 168h. The test results are shown in Table 2.

[0088] Table 2 Results of corrosion test on steel plate in nitrogen and oxygen environment

[0089]

[0090] It can be seen from Table 2 that the present invention improves the corrosion resistance of the coiled tubing by adjusting the elements of the raw materials.

[0091] Test Example 3

[0092] The hydrogen induced cracking (HIC) resistance of the weld of the coiled tubing of Example 1 was evaluated by taking samples at the weld position, 90° and 180° from the weld on the pipe, polishing the sample surface, and testing according to the NACETM0284 standard using solution A conditions. After immersion for 96 hours, the sample was taken out and the internal cracking of the sample was observed by the equal section method. The test results are as follows: Figure 7-12 shown.

[0093] Test conditions: P H2S =0.1MPa, solution is NACE-A, temperature is (25±3)℃, cycle is 96h.

[0094] Test process parameters:

[0095] The pH of the prepared solution was 2.75, the initial solution pH was 3.03, the initial hydrogen sulfide concentration was 2409 mg / L, the final solution pH was 3.65, and the final hydrogen sulfide concentration was 2512 mg / L.

[0096] Depend on Figure 7-12 It can be seen that there are a few cracks in the core of the sample at the weld position, but the crack rate meets the API5L requirements, and no cracks were found in the samples at 90° and 180° from the weld.

[0097] Test Example 4

[0098] The HIC test was performed on the coiled tubing (1#) of Example 1 and the coiled tubings CT80-1 (2#), CT80-2 (3#), and CT90 (4#).

[0099] (1) The HIC test is based on the standard NACE TM0284-2016, and the specific conditions are as follows:

[0100] Temperature 23℃~26℃, deoxygenated gas: 99.999% N2, test gas: 99.9% H2S, test solution A, test period 96h, hydrogen sulfide concentration in solution 2460mg / L, hydrogen sulfide concentration in solution 2396mg / L after saturation for 1h, initial pH value = 2.7, pH value at the beginning of the test = 2.9, pH value at the end of the test = 3.7, nominal size of the sample L×W×t (mm) = 100×20×4, sampling direction: longitudinal direction of the pipe body. The HIC test results are shown in Table 3.

[0101] Table 3 Coiled tubing HIC test results

[0102]

[0103] Test Example 5

[0104] Sulfide stress cracking (SSC) tests were performed on the coiled tubing (1#) of Example 1 and the coiled tubings of CT80-1 (2#), CT80-2 (3#), and CT90 (4#).

[0105] The standards are NACE TM0177-2016 and ISO 7539-2:1989 (four-point bending loading method). The specific conditions are as follows:

[0106] Temperature 23℃~26℃, pressure 1atm, deoxygenated gas: 99.999% N2, test gas: 99.9% H2S, test solution A, test period 720h, initial pH value = 2.7, test start pH value = 2.9, test end pH value = 3.7, sample nominal size L×W×t (mm) = 67.5×4.5×1.6, sampling direction: longitudinal direction of the tube body. The HIC test results are shown in Table 4.

[0107] Table 4 Sulfide stress cracking (SSC) test results

[0108]

[0109] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing, characterized in that: The sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing is manufactured by butting steel strips, curling, tube blank welding, extrusion, weld heat treatment, and cooling. The sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing includes, by mass percentage: C 0.04%~0.08%, Mn 1.5%~2.0%, Si 0.1%~0.3%, Cr 0.1%~0.3%, Mo0.05%~0.3%, Nb 0.04%~0.07%, Ti 0.005%~0.025%, Al 0.01%~0.05%, Ni≤0.3%, Cu≤0.3%, P≤0.02%, S≤0.02%, the balance is Fe and unavoidable impurities.

2. A method for preparing the sulfur-resistant and corrosion-resistant low-carbon alloy coiled tubing according to claim 1, characterized in that: The following steps are involved: S1. The steel strip is extended by butt welding, and the weld area is rolled and subjected to deformation heat treatment in sequence; S2, curling the steel strip obtained in S1 to form a round tube blank with a weld; S3, welding the round tube obtained in S2, adding an extrusion roller to the unsolidified rear of the molten pool to extrude the weld into shape; S4. The weld formed by the extrusion in S3 is heat treated, and after air cooling to room temperature, a sulfur-resistant and corrosion-resistant low-carbon alloy continuous oil pipe is obtained.

3. The preparation method according to claim 2, characterized in that: The butt welding in S1 is performed by plasma welding, and the welding wire used is a manganese-molybdenum steel high-strength copper-plated welding wire.

4. The preparation method according to claim 2, characterized in that: The rolling pressure in S1 is 4-8T, and it is repeated once.

5. The preparation method according to claim 2, characterized in that: The rolling deformation heat treatment in S1 refers to rolling the weld area while performing heat treatment, the rolling pressure is 4 to 8T, the rolling deformation heat treatment is repeated once, the rolling deformation heat treatment temperature is 600°C to 750°C, and the single rolling heat treatment insulation time is 10 seconds.

6. The preparation method according to claim 2, characterized in that: The weld gap of S2 is 1-2 mm.

7. The preparation method according to claim 2, characterized in that: The welding in S3 is laser welding or high frequency welding.

8. The preparation method according to claim 2, characterized in that: The heat treatment in S4 is simulated normalizing and tempering, wherein the treatment temperature of the simulated normalizing is 900°C to 940°C, and the tempering treatment temperature is 500°C to 600°C.

9. The preparation method according to claim 8, characterized in that: The treatment temperature of the simulated normalizing is 910°C, and the tempering treatment temperature is 550°C.

10. The preparation method according to claim 8, characterized in that: The treatment temperature of the simulated normalizing is 940°C, and the tempering treatment temperature is 550°C.